New Plants for Florida: Sugarcane - Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
In 2000, Florida produced 450,000 acres of sugarcane with an estimated value of $750 million. Canal Point clones occupied 75% of Florida's sugarcane area, accounting for $560 million in farm income. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.